E-Government As A Form Of Smart Governance Implementation At Bandung Smart City - Arjuna Arief Kesuma; Arief Sukma Yulianto; Sapta Dwi p (Publikasi Indonesia, 2023)
An innovative step in achieving the total realization of E-government is not only carried out through generating an idea and mutual agreement between government institutions in the city of Bandung. The government must also pay careful attention to the factors that underlie the government's actions. Apart from fulfilling digital services based on information technology, the government must also be able to predict what will later cause the gap between public needs and the reality that occurs during the process—implementation of E-Government for the Bandung Smart City program. Through a literature study approach, this research focuses on theoretical development and by collecting secondary data, the results of the research have shown that the Bandung City Government has continuously attempted to optimize E-Government by strengthening regulations and continuous evaluation, which in turn will optimize the accountability of public services based on information technology in each area in the city of Bandung and also maximize the implementation of the Bandung Smart City concept by minimizing community gaps in each area in the city implementation of the Bandung Smart City concept by minimizing community gaps in each area in the city.